EFFECT OF EPIDERMAL GROWTH FACTOR AND INSULIN ON IN VITRO MATURATION OF CAPRINE OOCYTES AND PRE IMPLANTATION EMBRYO DEVELOPMENT - PALANISAMMI, A; RANGASAMY, S; REENA, D; GOPIKRISHNAN, D (The Indian Journal of Animal Reproduction, 2023)
Totally 1362 oocytes were collected from 358 goat ovaries obtained from abattoir, by slicing technique.The overall culturable oocytes recovery rate per ovary was 2.02.ln experiment l(EGF @ 10 ng per ml), thenumber of inseminated oocytes cleaved day 1-2 were 145 embryos at 2-4 cell stage, 112 embryos at 8 cellstage on day 3, 75 embryos at 16-32 cell stage on day 4-5, 46 embryos at blastocyst stage on day 6-7.lnexperiment ll(insulin@ 1 μg per ml), the number of inseminated oocytes cleaved at day 1-2 were 151 embryosat 2-4 cell stage, 123 embryos at 8 cell stage on day 3, 83 embryos at 16-32 cell stage on day 4-5 and 57embryos at blastocyst stage on days 6-7.lnexperiment Ill (control) the number of inseminated oocytes cleavedat day 1-2 were 154 embryos at 2-3 cell stage, 98 embryos at 8 cell stage on day 3, 62 embryos at 16-32cell stage on day 4-5 and 31 embryos at blastocyst stage on day 6-7. Thus supplementationof growth factorsEGF and insulin to maturation and culture media can increase in vitro maturation rate and improve the embryodevelopment rate in caprine.
Keywords: Caprine; Epidermal growth factor; Insulin and Embryo development